2014
DOI: 10.1002/iub.1335
|View full text |Cite
|
Sign up to set email alerts
|

Tumour suppressors and cellular senescence

Abstract: Cellular senescence is a stable cell cycle arrest that normal cells undergo in response to a variety of intrinsic and extrinsic stimuli, including progressive telomere shortening, changes in telomeric structure or other forms of genotoxic as well nongenotoxic stress. Senescence is thought to have originated as a remodelling program that is active in embryonic development and acts as a key tumour suppressor mechanism during the reproductive stage in early adult life, by leading to the removal of potentially can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 102 publications
0
8
0
Order By: Relevance
“…In conclusion, cell senescence reduces the age-related tumor development and contributes to human aging, suggesting that aging might be switched for tumorigenesis [ 201 , 202 ]. ROS may modulate tumor suppression process, which is induced by the senescence, thus participating in anticancer mechanisms, although ROS may act as tumor promoters in definite conditions [ 48 ].…”
Section: Ros In Cell Senescencementioning
confidence: 99%
“…In conclusion, cell senescence reduces the age-related tumor development and contributes to human aging, suggesting that aging might be switched for tumorigenesis [ 201 , 202 ]. ROS may modulate tumor suppression process, which is induced by the senescence, thus participating in anticancer mechanisms, although ROS may act as tumor promoters in definite conditions [ 48 ].…”
Section: Ros In Cell Senescencementioning
confidence: 99%
“…Although senescent cells play an important role in tumour suppression and some unsuspected aspects of normal physiology 48 50 , they are central players both in age-related mortality and in various forms of morbidity (for example, as causal agents of adverse reactions to chemotherapy). However, data on their phenotype and behaviour fall far short of what is required if therapeutic progress is to be made in a reasonable timescale.…”
Section: Cell Senescence: Where Next?mentioning
confidence: 99%
“…5 p53 is a transcription factor which was initially identified as an oncogene. 6 Further studies have confirmed that it is a tumor suppressor 7 associated with anti-inflammatory activities. 8 Indeed, p53 attenuates NF-kappaB activation and ALI.…”
mentioning
confidence: 95%
“…The understanding of those molecular cascades which govern the permeability of the vascular wall; may reveal novel ways to counteract ARDS . p53 is a transcription factor which was initially identified as an oncogene . Further studies have confirmed that it is a tumor suppressor associated with anti‐inflammatory activities .…”
mentioning
confidence: 99%